Pengaruh Musik Mozart dalam Mengurangi Stres pada Mahasiswa yang Sedang Skripsi - Rina Rosanty (Universitas Ahmad Dahlan, 2014)
AbstractÂ This study aims for determining the effect of Mozart classical music to decrease the stress level among sixteen students who are writing their thesis. The present study used a randomized pretest posttest control group design. The process of Mozart classical music was conducted in four sessions for 1 hour. The score of stress level was analyzed to compare between pretest, posttest and follow up using Friedman test. The result of data analysis showed a significant decreasing of stress level score between pretest, posttest and follow up in the experimental group (Chi-Square = 12,542 p = 0,02 p < 0,05). This result indicated that Mozart classical music was quite effective in decreasing stress among students who is writing their thesis.Keywords: Mozart classical music, stress among students who are writing the thesis